Vietnam’s foreign policy and its Ukrainian aspect in the context of the historical and political processes of modern time - Andriy Kudryachenko; Yevhen Prypik (Cхід, 2020)
The article examines the process of forming Vietnam’s foreign policy in the context of the historical and political processes of the country in recent history. Paying tribute to the Asian conservatism and seeing a reform of the political system as a threat to the foundations of the statehood and national unity, the Vietnam leaders has chosen its path of social modernization - a “renovation” strategy (in Vietnamese - “Đổi Mới”) that has transformed the country within twenty years into another Asian tiger. The “renovation” course was to allow the policy of “open doors” in foreign economic relations. External factors for the successful development of the Vietnam’s foreign policy include the ASEAN membership. Due to the many political and socio-cultural factors common to Vietnam and the ASEAN member states (Vietnam joined ASEAN in 1995) and the continued political stability of the country, Vietnam has achieved a particular favor from the investors and trading partners of this association. Considerable attention in the article has also been paid to analyzing the development of political and trade-economic relations between Vietnam and Ukraine in the context of multilateral cooperation. The establishment of diplomatic relations between the two countries and signing the key bilateral agreements has been analyzed. The absence of fundamental differences on key international issues as well as the willingness to develop friendship and mutually beneficial partnership has created the favorable conditions for cooperation between Ukraine and Vietnam within the international organizations. There is much in common in our countries’ positions on the proliferation of nuclear weapons and other weapons of mass destruction, counter-terrorism, reform of the United Nations etc. Ukraine and Vietnam have traditionally supported each other’s nominations for election to the governing bodies of international organizations.